Assessment on Qualities of Drinking Water, Ambient Air, and River in Select Barangays in Mariveles, Bataan, Philippines - Arlene A. Zabala (Indonesian Journal of Social and Environmental Issues (IJSEI), 2025)
This quantitative study, employing a Descriptive-Survey Design, investigates assessments on drinking water, ambient air, and river in three barangays - Alas-Asin, Baseco, and Sisiman - within Mariveles, Bataan. A survey-questionnaire instrument, divided into five sections, evaluates various aspects, including water quality, ambient air quality, their effects on health and community, barangay river quality, and respondents’ awareness of environmental initiatives. With a sample size of 900 respondents, 300 from each barangay, statistical analysis reveals concerning findings regarding access to safe drinking water, air and water quality issues, and limited community awareness. Recommendations include enhancing access to safe drinking water, improving air quality monitoring, strengthening community engagement, fostering partnerships, and regularly monitoring environmental projects. This research stresses the urgent need for proactive measures to address environmental challenges and promote sustainability in Mariveles, Bataan, emphasizing collaboration among stakeholders for lasting positive change.